Technologies For Creating Educational Software Tools Using Author's Programs - Yuldasheva G. T.; Yuldasheva S. R. (Euro Asian Journal Publishing, 2025)
This paper examines technologies for creating educational software tools using author's programs. The main principles of development, advantages and disadvantages of such programs, as well as their application in the educational process are considered. Particular attention is paid to methods for developing software tools that can be used in teaching mathematics and computer science in pedagogical universities
Keywords: author's programs; educational software; development technologies